Нанокомпозити, отримані реакційним спіканням кубічного нітриду бору з алюмінієм і диборидом титану - Беженар, М.П.; Гарбуз, Т.О.; Коновал, С.М.; Божко, С.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
It is analyses of problems and achievements of receipt of cubic boron nitride nanocomposites
in systems cBN-Al and cBN-Al-TiB2 at high pressure and temperature.